Developing a mental game plan: Mental periodization for achieving a "flow" state for the track and field throws athlete - Judge, L. W.; Bell, R. J.; Bellar, D.; Wanless, E. (The Sport Journal, 2010)
Athletes participating in all levels of sport experience extraordinarily high levels of stress, expectations, and physical challenges. The throws event athlete in track and field should strive to achieve an optimal state of arousal and concentration during specific competitions. A strong body of research evaluating the qualities of the flow state in athletics and psychological skills training is present in sport psychology. A practical guide for coaches to apply psychological skills training in a periodized training plan is missing. The purpose of this article is to: 1) describe a periodized annual plan for mental skills training and 2) suggest a method to interject those skills into the competition day routine to achieve flow for the track and field thrower.